Cholinergic modulation in the vertebrate auditory pathway - Zhang, Chao; Burger, R. Michael (Frontiers in Cellular Neuroscience, 2024)
Acetylcholine (ACh) is a prevalent neurotransmitter throughout the nervous system. In the brain, ACh is widely regarded as a potent neuromodulator. In neurons, ACh signals are conferred through a variety of receptors that influence a broad range of neurophysiological phenomena such as transmitter release or membrane excitability. In sensory circuitry, ACh modifies neural responses to stimuli and coordinates the activity of neurons across multiple levels of processing. These factors enable individual neurons or entire circuits to rapidly adapt to the dynamics of complex sensory stimuli, underscoring an essential role for ACh in sensory processing. In the auditory system, histological evidence shows that acetylcholine receptors (AChRs) are expressed at virtually every level of the ascending auditory pathway. Despite its apparent ubiquity in auditory circuitry, investigation of the roles of this cholinergic network has been mainly focused on the inner ear or forebrain structures, while less attention has been directed at regions between the cochlear nuclei and midbrain. In this review, we highlight what is known about cholinergic function throughout the auditory system from the ear to the cortex, but with a particular emphasis on brainstem and midbrain auditory centers. We will focus on receptor expression, mechanisms of modulation, and the functional implications of ACh for sound processing, with the broad goal of providing an overview of a newly emerging view of impactful cholinergic modulation throughout the auditory pathway.